A Comprehensive Review of Techno-Economic Perspective of AC/DC Hybrid Microgrid - Zaman, Md Rakibur; Sarker, Sudip; Halim, Md Abdul; Ibrahim, Salah; Haque, Abrarul (Control Systems and Optimization Letters, 2024)
The main objective of this research is to review the techno-economic aspects of AC/DC hybrid microgrid. This review has been done by scrutinizing the essential constituents of both AC and DC microgrids, accentuating their corresponding benefits and constraints. The benefits and reasons for integrating AC and DC technology in a hybrid microgrid setting are then covered. From a technological standpoint, the study addresses Renewable Energy Integration, Power Electronic Converters, Energy Storage Systems, Control and Energy Management system and Grid Synchronization. This can lead to a reduction in the overall operational expenses of the microgrid, making it more economically viable in the long run. Initial Investment, Life cycle costs, Payback period, Operational and Maintenance Costs, Regulatory Incentives and Policies and energy savings cost regarding the financial aspect has been reviewed in this paper. complexity to design, operation, and control is a big challenge of AC/DC Hybrid Microgrid. Challenges in the smooth integration of AC and DC components have also been reviewed. The study also investigates how different regulations, laws, and incentives affect the financial sustainability of AC/DC hybrid microgrid projects. Real-world examples and case studies are included to offer useful insights into the effectiveness and viability of current AC/DC hybrid microgrid systems from an economic standpoint. In addition, the review points out areas of current research deficiency and makes recommendations for future directions in this area of study. Researchers, practitioners, and policymakers interested in the design and implementation of resilient and sustainable energy systems will find great value in the thorough review that presents the current level of knowledge on the techno-economic aspects of AC/DC hybrid microgrids. The review's conclusions can be used by legislators to create well-informed rules and policies that encourage the installation of AC/DC hybrid microgrids and their integration with the current energy infrastructure. When designing, developing, and implementing AC/DC hybrid microgrid systems, researchers and technology developers can recognize important obstacles as well as opportunities.